A case study of excellence in elite sport: Motivational climate in a world champion team - Hodge, K.; Henry, G.; Smith, W. (The Sport Psychologist, 2014)
This case study focused on the New Zealand All Blacks rugby team during the period from 2004 to 2011, when Graham Henry (head coach) and Wayne Smith (assistant coach) coached and managed the team. More specifically, this case study examined the motivational climate created by this coaching group that culminated in winning the Rugby World Cup in 2011. In-depth interviews were completed with Henry and Smith in March 2012. A collaborative thematic content analysis revealed eight themes, regarding motivational issues and the motivational climate for the 2004-2011 All Blacks team: (i) critical turning point, (ii) flexible and evolving, (iii) dual-management model, (iv) "Better People Make Better All Blacks," (v) responsibility, (vi) leadership, (vii) expectation of excellence, and (viii) team cohesion. These findings are discussed in light of autonomy-supportive coaching, emotionally intelligent coaching, and transformational leadership. Finally, practical recommendations are offered for coaches of elite sports teams.